Situational Leadership, Contingency, Organizational Effectiveness, and Adaptation to Curriculum Change - Wardana, Fuad Kusuma; Muhammad, Muhammad; Agus, Agus (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The study results show that situational leadership plays a crucial role in determining leadership strategies and styles appropriate to the teacher's level of preparedness and the school's organizational conditions of contingency theory provides an understanding that leadership effectiveness depends on the fit between leadership style and organizational situation. Both complement each other in creating organizational effectiveness, which is characterized by increased teacher performance, team collaboration, and the achievement of educational goals. Furthermore, adapting to curriculum changes requires adaptive, communicative, and visionary leadership to manage change, minimize resistance, and build a culture of innovation within the school environment. Therefore, integrating situational leadership and a contingency approach is an effective strategy for strengthening educational organizations' ability to navigate curriculum change. Thus, flexible and contextual educational leaders play a strategic role in creating resilient, responsive organizations oriented toward improving educational quality in the current era of educational transformation.